Effect of heat treatment cycles on tensile performance and microstructural evolution of thixoformed MWCNT-A356 composite - Hashim, Hanizam; Salleh, Mohd Shukor; Marjom, Zolkarnain; Boejang, Hambali; Sundi @ Suandi, Syahrul Azwan; Abdul Rasib, Amir Hamzah; Sulong, Abu Bakar; Omar, Mohd Zaidi (Taylor's University, 2023)
A liquid casting of multi-walled carbon nanotubes (MWCNT)-A356 alloy composite is an excellent alternative in the production of automotive parts. The casting process begins by premixing the MWCNT and magnesium powder as reinforcement and wettability agent, respectively before inserted into the liquid matrix. Mechanical stirring promotes uniform distribution of MWCNT and forming the non-dendritic microstructure by convection and shearing forces. Thixoforming process was carried out at 50 % of liquid fraction followed by T5 and T6 heat treatment cycles. Composite grain structure and intermetallic phases were characterized using an optical microscope and X-ray diffraction procedures. Meanwhile, the investigations of MWCNT distribution and tubular structural integrity on tensile test fracture samples using the field-emission microscopic and Raman spectroscopy were uniformly distributed and with minimum damage. The ultimate tensile strength (UTS) of thixoformed composites after T5 and T6 were improved by 7.2% (270.5 MPa) and 30.8% (330.3 MPa), respectively. The enhancement of T6 is higher than T5, corroborating with the isothermal holding at 540 °C during the solution treatment permits the further dissolution of eutectic α-Al and precipitates, allows better distribution of MWCNT and promotes higher strengthening mechanisms.